Efficacy of plant extracts on Sclerotium rolfsii, the seedling blight of tea - Bhagat, Indramani (Nepalese Journal of Biosciences, 2013)
The fungus Sclerotium rolfsii is one of the most destructive diseases in tea growing areas of the world. Effective and efficient management of cash crop disease is generally achieved by the use of synthetic pesticides. These pesticides are known to pollute the environment, soil and water causing deleterious effects on human health and biosphere. A search for an environmentally safe and economically viable strategy for the control of the disease has led to an increased use of plant based products in agriculture. Hence, in the present investigation, efficacy of antifungal effect of Azadirachta indica and Catharanthus roseus were tested in vitro against S. rolfsii.